The effect of contraceptive use on women empowerment, as measured by educational attainment - Castellon, Julia Antonina P.; Sason, Robyn Lyanna F.
The Philippines has one of the highest fertility rates among minors in Southeast Asia. Multiple studies have shown that this can be attributed to minors engaging in unprotected sex, which can be a symptom of institutional weaknesses that have made family planning methods inaccessible to individuals who need it. As a result, these high fertility rates have hindered educational attainment and become, therefore, detrimental to women empowerment. This research, then, analyzes the effects of using family planning methods (i.e. contraceptive use) on women empowerment, as measured by their educational attainment. Using the National Demographic and Health Survey 2017, the study sample consisting of sexually-active women aged between 18 and 19 was obtained. A binary logistic regression analysis was used to study the effects of contraceptive use on secondary or higher education completion rates. Other exogenous variables were considered for the empirical model as well. Results show that two of the three dummy variables used for contraceptive use are significant - the current non-use of contraception with intentions for future use at the 5% level and the current use of modern contraception at the 1% level. Other exogenous variables also prove to be significant. Due to the results of this study, the researchers conclude that contraceptive use, modern contraceptive use in particular, does have a significant effect in increasing the likelihood of attaining High school education and, in turn, women empowerment. Therefore, the researchers recommend further study into the policy implications of easing access and providing quality training on proper use of modern contraceptives to maximize the positive effects on educational attainment.